Production of Biofir Bottled Drinking Water in UD. Sumber Mubarokah Sidoarjo Perspective of Islamic Economic System - Muhammad Al Faruq; Muhammad Hamdan Ali Masduqie; Fatikul Himami Himami; Vivin Maharani Maharani Ekowati; Masyhuri Machfudz Machfudz (ITB AAS INDONESIA Surakarta, 2023)
The research conducted aims to determine the production process of BIOFIR bottled water in UD. Sumber Mubarokah Sidoarjois reviewed from the principles of Islamic production and the implementation of the Islamic economic system regarding the basic and instrumental values of Islamic economics. Research methods used in research conducted on UD. Sumber Mubarokah Sidoarjo uses a descriptive qualitative approach with a type of case study research on objects. The data collection techniques are through interviews with informants, both in person and online media, direct observation at the informant's place, documentation in the form of photos related to drinking water production business activities carried out by UD. Sumber Mubarokah Sidoarjo as complementary evidence in the research, and triangulation of the methods used by researchers to unearth the truth of business owner informants. The results of the research obtained in this study are the production process of BIOFIR bottled drinking water at UD. Sumber Mubarokah Sidoarjohas been quite good and meets the provisions of production in an Islamic manner. Other results show that islamic principles of production have been applied and the basic and instrumental values of Islamic economics have been applied to the factors of production. Keywords: Production, Bottled Drinking Water and Islamic Economic System.